Effectiveness of Betel Leaf Extract (Piper betle L.) against bacterial infection (Vibrio paraharmolyticus) in Vaname Shrimp (Litopenaeus vannamei) - Panduwinata, Vina; Hadijah, St; Harlina, Harlina; Hamdillah, Andi; Ilmian, Ilmian (Agrikan Jurnal Agribisnis Perikanan, 2025)
This research aims to identify the types of bioactive compounds in the methanol extract of betel leaves (Piper betle L) observing the Clear Zone. And knowing the inhibitory ability of methanol extract of betel leaves (Piper betle L). through determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against V. parahaemolyticus. This research used experimental methods and completely random sampling (RAL). By carrying out a GC-MS test to identify the bioactive compounds contained in betel leaves. Antibacterial activity test and minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) tests to determine the ability of betel leaf extract to inhibit Vibrio parahaemolyticus bacteria. And a challenge test to determine the survival rate. The results of descriptive analysis and Anova statistical tests show that betel leaf extract contains 5 secondary metabolic compounds. The use of betel leaf extract 10 mg/ml, 15 mg/ml, 20 mg/ml shows strong inhibitory power with a minimum concentration of 3.12 mg/ml and 6.25 mg/ml after the Survival Rate challenge test was carried out for vaname shrimp treated with 85% betel leaf extract, while the administration of betel leaves was also able to reduce the clinical symptoms experienced by vaname shrimp with a concentration of 50 mg/ml. Conclusion: These results identify that betel leaf extract has secondary metabolic compounds that can be used as antibacterials in white shrimp cultivation activities.